2015
DOI: 10.1016/j.shaw.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Comorbid Health Problems and Musculoskeletal Disorders Resulting in Musculoskeletal Complaints and Musculoskeletal Sickness Absence among Employees in Korea

Abstract: BackgroundTo investigate the relationship between musculoskeletal disorders and comorbid health problems, including depression/anxiety disorder, insomnia/sleep disorder, fatigue, and injury by accident, and to determine whether certain physical and psychological factors reduce comorbid health problems.MethodsIn total, 29,711 employees were selected from respondents of the Third Korean Working Conditions Survey and categorized into two groups: Musculoskeletal Complaints or Musculoskeletal Sickness Absence. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
4
14
1
3
Order By: Relevance
“…Poor or limited sleep is recognised as a potential contributor to a range of chronic conditions, including musculoskeletal complaints [38,39]. The majority of patients (52.9%) self-reported having 7-8 h of sleep per night and this is consistent with work by Adams et al [40] in an Australian community sample.…”
Section: Behavioural Determinants Of Healthsupporting
confidence: 69%
“…Poor or limited sleep is recognised as a potential contributor to a range of chronic conditions, including musculoskeletal complaints [38,39]. The majority of patients (52.9%) self-reported having 7-8 h of sleep per night and this is consistent with work by Adams et al [40] in an Australian community sample.…”
Section: Behavioural Determinants Of Healthsupporting
confidence: 69%
“…The study also shows an association between MSDs and occupational stress. This finding is confirmed by Leclerc et al (1999), Baek et al (2015), and Bongers et al (1993), all of whom reported an association between psychological stress and MSDs. When adjusted for demographic and occupational variables in the bivariate logistic regression model, the findings suggest that occupational stress is less likely to be experienced by members of the comparison groups as compared to the mine workers.…”
Section: Discussionsupporting
confidence: 58%
“…Mental stress diverts resources spent on attention, and can lead to fatigue and injury (1,19). Study reported the significantly higher prevalence of depression, sleep disorders and occupational accidents among workers who had MSDs compared to those who did not (27). It is increasingly evident that addressing psychological factors impacting workers, is crucial for prevention of persistent MSDs.…”
Section: Factors Related To the Risk Of Persistent Msdsmentioning
confidence: 99%